Food estate dalam Bingkai Media: (Analisis Framing Pada Media Online Waspada.co.id) - Andinata, Maulana; Syam, Abdi Mubarak; Ramadhan, All Rizky (Jurnal Kajian Agraria dan Kedaulatan Pangan (JKAKP), 2023)
Media has a very central role in defining how reality should be understood and how that reality should be explained in a certain way to the public. The dynamics of the pros and cons of food estate seems interesting to examine further from Waspada.co.id’s perspective in framing information related to food estate. The research method used in this study is the framing analysis model, with reference to four aspects, namely; Define Problems, Diagnose Cause, Make Moral Judgment, and Treatment Recommendation. The results of the research show that Waspada.co.id has tried to be balanced in presenting information, but on the other hand the majority actors such as private corporations are given a large enough space, accusing the various opinions expressed by local residents as inappropriate. Waspada.co.id seems inclined to construct or frame the Food estate program as an important program and has a priority scale in government programs, especially after the Covid-19 pandemic. This can be seen through the construction of Waspada.co.id news which selects and emphasizes certain positive aspects of the food estate program.